New perspective: Symbiotic pattern and assembly mechanism of Cantharellus cibarius-associated bacteria - Ge, Wei; Ren, Yulian; Dong, Chunbo; Shao, Qiuyu; Bai, Yanmin; He, Zhaoying; Yao, Ting; Zhang, Yanwei; Zhu, Guosheng; Deshmukh, Sunil Kumar; Han, Yanfeng (Frontiers in Microbiology, 2023)
Cantharellus cibarius is a valuable ectomycorrhizal fungus belonging to the Basidiomycetes, which has significant medicinal and edible value, economic value, and ecological benefits. The unique evolutionary history and artificial domestication of C. cibarius have attracted many researchers to carry out a large number of studies on its ecology, phylogeny, and bacteria. However, the rare taxa, symbiotic patterns, and assembly mechanisms of bacteria remain unknown. In this work, we divided bacterial taxa into abundant and rare taxa and analyzed the diversity of bacterial taxa in the fruiting body and mycosphere. The null model and interaction network were used to reveal the assembly and co-occurrence patterns of abundant and rare bacterial communities respectively. PLS-PM was used to construct the effect of abiotic factors on the diversity of different taxa, and METAGENassist2 was used to characterize the potential metabolic functions and phenotypes of two types of sample-abundant and rare bacteria. The results revealed that the mycosphere's bacterial diversity was greater than that of the fruiting body, and the diversity of rare bacterial taxa was greater than that of abundant bacterial taxa in both types of samples. The assembly of abundant and rare bacteria in fruiting bodies and mycospheres was dominated by dispersal limitation. The co-occurrence patterns of bacteria in the mycosphere may be more complex than those found in fruiting body samples. In addition to the specific potential functions of abundant bacteria, rare bacteria may provide complementary or unique metabolic pathways to sustain the ecological function of C. cibarius. It is important to note that while volatile organic compounds (VOCs) can hinder the bacterial diversity of the mycosphere, they can boost the bacterial diversity of the fruiting body. These results provide new and relevant insights into ectomycorrhizal fungi such as C. cibarius and their associated microbial ecology.